Establishment of a thermal process for bottled balao-balao (fermented rice-shrimp mixture) - Santos, Ma. Anna Rita T. (2004)
ABSTRACT Balao-balao is a fermented mixture of rice and shrimp used mainly as a condiment but may also be served as the main dish. Thermal processing will be useful in prolonging the shelf-life of the product, which will enable the producers to market the bottled balao-balao outside of their town or even out of the country. This leads to the general objective of the study, which is to establish a thermal process for bottled balao-balao. To attain this general objective, the initial characteristics of the product like pH, titratable acidity and general appearance, was first obtained and a reference organism was identified. Heat penetration tests were then done on the product using 10, 20 and 30 minutes of processing times. To determine which process is adequate, the processes were evaluated together with microbiological, physico-chemical, and sensoy analysis. After the process evaluation, it was found that the 10-minute process was the least time required to kill the reference organism and render the product commercially safe. Microbiological examination showed all processes had no considerable number of significant organisms and the most overall acceptable in terms of sensory characteristics was the product processed for 10 minutes. Based from these, it can then be concluded that processing the bottled balao-balao at 10 minutes is enough to produce a product that is microbiologically safe and acceptable.